"Diagnosing" Saudi health reforms: is NHIS the right "prescription"?. (10th October 2012) - Al‐Sharqi, Omar Zayan; Abdullah, Muhammad Tanweer
SUMMARY: This paper outlines the health context of the Kingdom of Saudi Arabia (KSA). It reviews health systems development in the KSA from 1925 through to contemporary New Health Insurance System (NHIS). It also examines the consistency of NHIS in view of the emerging challenges. This paper identifies the determinants and scope of contextual consistency. First, it indicates the need to evolve an indigenous, integrated, and comprehensive insurance system. Second, it highlights the access and equity gaps in service delivery across the rural and remote regions and suggests how to bring these under insurance coverage. Third, it suggests how inputs from both the public and private sectors should be harmonized – the "quality" of services in the private healthcare industry to be regulated by the state and international standards, its scope to be determined primarily by open‐market dynamics and the public sector welfare‐model to ensure "access" of all to essential health services. Fourth, it states the need to implement an evidence‐based public health policy and bridge inherent gaps in policy design and personal‐level lifestyles. Fifth, it points out the need to produce a viable infrastructure for health insurance. Because social research and critical reviews in the KSA health scenario are rare, this paper offers insights into the mainstream challenges of NHIS implementation and identifies the inherent weaknesses that need attention. It guides health policy makers, economists, planners, healthcare service managers, and even the insurance businesses, and points to key directions for similar research in future. Copyright © 2012 John Wiley & Sons, Ltd.